DESCRIPTION OF SOCIO-LEGAL FACTORS LEADING TO DIVORCE (Neo Scientific Peer Reviewed Journal, 2025)
The article analyzes the various relationships between husband and wife in divorce. In particular, some factors that cause divorce: the intervention of other people, divorce due to financial difficulties in the family have been widely criticized.